Genetic characterization of measles virus strains isolated during an epidemic cluster in Puglia, Italy 2006–2007 - Chironna, Maria (BioMed Central, 2007)
The genetic characterization of wild-type measles strains isolated during an epidemic cluster of measles occurred in Puglia (South Italy), between November 2006 and January 2007, was performed. Measles virus (MV) detection was carried out by a nested RT-PCR on 8 of 18 total cases. The viruses were analyzed using the standard genotyping protocols. The N gene sequences of the strains from outbreak were identical to each other, and sequence analysis revealed that the viruses belonged to genotype B3, subgroup B3.1, never identified before in Italy. An importation of measles B3.1 strains from Africa was hypothesized. Molecular surveillance will help to monitor the progress in measles elimination.